The Impact of the Implementation of P5-PPRA in Strengthening the Attitude of Religious Moderation of Students at MAN 2 Langsa - Rahimah, Anna; Sabaruddin, Sabaruddin; Mukhlis, Mukhlis (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study examines the effects of the Pancasila Student Profile and Rahmatan lil 'Alamin Student Profile (P5-PPRA) Strengthening Project on enhancing religious moderation at MAN 2 Langsa. This study addresses the gap in research that typically emphasizes varied interfaith schools by examining a relatively religiously homogeneous madrasah, focusing on intra-community diversity. The research employs a qualitative methodology utilizing a field case study design; data is collected by observation, interviews, and documentation, subsequently analyzed inductively through thematic coding, with triangulation for validating sources, procedures, and temporal aspects. The findings indicate discrepancies in teacher practices: some implement values in a systematic and contextual manner through learning and projects, whereas others remain implicit and administrative. Institutional support, including religious habituation (Yasinan) and the practice of fardhu kifayah, enhances social responsibility, mutual collaboration, and discipline in worship. From the student's viewpoint, collaborative projects such as calligraphy, recycled art, eco-friendly soap production, and the practice of fardhu kifayah function as a means to internalize principles that promote acceptance of diversity, debate, deliberation, and peaceful conflict resolution. Emerging challenges included disparities in literacy regarding moderation, ineffective assessment of values, lack of synchronization among educators, constrained time and resources, and the financial burden associated with certain activities.